Body dissatisfaction and quality of life in adolescents students:: systematic review - Rosales-Damian, Guillermo; Torres-Chávez, Lilia Janeth; Hidalgo-Rasmussen, Carlos Alejandro (Pensando Psicología, 2025)
Objective. This systematic review aimed to synthesize evidence on the relationship between body dissatisfaction and health-related quality of life (hrqol) in adolescent students. Method. Following the PRISMA methodology, quantitative studies on students aged 13 to 18 were considered, with no publication year restrictions, in both English and Spanish were analyzed. Searches were conducted in Scopus, ScienceDirect, PubMed, and Web of Science. Results. Five studies were included, demonstrating a direct relationship: greater body dissatisfaction is associated with lower hrqol. This is because a negative body image reduces self-esteem, self-confidence, and psychological well-being. Longitudinal studies and the inclusion of additional variables are recommended to further explore this relationship.
Keywords: body image; body dissatisfaction; quality of life; Students; systematic review